PENGAYOMAN PEMERINTAH PADA MASYARAKAT DALAM MEWUJUDKAN DESA TANGGUH BENCANA - Anggoro, Ayub Dwi; Susanto, Happy; Arifin, Rizal; Nugroh, Oki Cahyo; Purwati, Eli; Ridho, Irvan Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This activity has a focus on strengthening the community's role in creating a disaster-resilient village in Dayakan Village, Badegan District, Ponorogo Regency. The main benefit of this activity is to rebuild the community's contribution in the context of disaster management in Dayakan Village. Desa Dayakan is one of the villages which is affected by natural disasters every year such as landslides, flash floods, forest fires, and droughts. The entire Dayakan Village is located on the contours of mountainous land and most of it is forest. The implementation of this service is carried out through several activities including: (1) Socialization of program activities, (2) Strengthening the existence of disaster risk reduction (DRR) forums, (3) Disaster and emergency mitigation training, (4) Establishment of disaster posts in each hamlet, and (5) Establishment of disaster communication and information posts. In practice, the community has been very supportive of this activity through their participation in every activity held, besides that the role of the village government, DRR groups, and external institutions has also continued to be developed. The advice given in this activity is that the village government must be the motor in giving enthusiasm to the community to make the area a disaster resilient village.Keywords: Disaster Resilient Area, Community, Role